The Role of Environmental Administration Law: A Study of Environmental Struggle of the Awyu Tribe - Putra, Arsyi Manggali Arya; Prawira, Suwiryo; Rohman, Rohman; Rafiqi, Ilham Dwi (Hang Tuah Law Journal, 2025)
One of the most fundamental environmental problems is the deviation in the application of state administrative law. As a result, there are environmental problems experienced by the Awyu Tribe who are affected by the licence of an oil palm plantation company. Especially during the preparation of the Environmental impact assessment form State Administrative Decree did not provide participation to Awyu Tribe. Therefore, this research aims strengthen the role of administrative law in providing legal protection guarantees for the Awyu Tribe affected by oil palm plantation permits and the role of administrative court as downstream protection of the community by government actions. This research uses normative legal research methods with statutory and conceptual approaches and the analysis technique descriptive qualitative. The results showed that administrative law as basic foundation for issuance of state administrative decisions stipulated in Article 87 of Law No. 30/2014 must pay attention to impact of issuance of state administrative decisions, especially human rights. Judges judgments in the Awyu Tribe case tend to be positivistic and not progressive in favour private parties. Judges in deciding environmental cases also apply the values of the General Principles of Good Governance and community participation. In addition, laws and regulations on environmental protection and management are umbrella provisions that have not provided welfare for the Awyu people. The presence of administrative law should be able to provide public protection against environmental cases, because the two laws and regulations have continuity. Judges must be able to apply the value of both rules an effort to protect and prosper the community.